Sharing Session Tata Tulis Karya Ilmiah: Meningkatkan Ide dan Kreativitas Dalam Menyusun Karya Tulis Ilmiah - Nugroho, Handi Wilujeng; Hamidi, Kurniawan; Nasution, Rivarra Syara; Kurniadi, Deri; Saputri, Anggraini Dwi (Faculty of Engineering University of Pahlawan Tuanku Tambusai, 2023)
This activity aims to increase students' insight into the importance of writing scientific papers, good scientific writing techniques, and how to use appropriate references. This event will be held online via the Zoom application on July 29 2023 with the theme